Elaboración de Balanceados a partir de productos infrautilizados con Colocasia esculenta y Manihot esculenta para cerdos en la etapa de engorde. - Víctor Hugo, Ulcuango Granizo (2022)
Balanced foods intended for the nutrition in animal farming industry have been the object of study for the past years due to the increase in the rate of consumption of pork meat and the usage of underused products from the area . This can contribute to a better profitability for producers also making it necessary to implement new techniques that would involve the usage of underused raw materials in animal farming fed , improving all production costs as well as performance in terms of food consumption and meat conversion, for these reasons, the research has been elaborated in order to develop a feed formulation for pigs in the fattening stage (for 30 days) based on underused products such as Chinese potato (Colocasia esculenta) and cassava (Manihot esculenta), with an amount of feed that corresponded to 2 .5 kg per pig divided into three stages of the day (06:00; 12:00 and 18:00). Through an analysis of the components that form balanced food, a descriptive experimental field investigation was conducted to measure variables such as weight and height, with the preparation of formulas and the adecuate control of the initial sample T0 (commercial balanced of PRONACA), which served to analize the data critically following that analysis a completely random statistical model was applied with 4 treatments, which were coded as (T0, T1, T2, T3) with 3 repeated testings. To assure the accuracy of the results an ANOVA study was applied as well as a Tukey's test at 0.05 (significance index) with right tail analysis. For the methodology of the research, a null hypothesis was raised determining as a result that T3 had a 44.22% average weight gain better than all treatments as well as an average meat conversion of 12.07% in contrast to the control treatment (T0) which obtained values of 43.12% in average weight gained and a conversion of 13.19%, the result of the investigation determined that (T3) was the best treatment constituted by a 15% of Yucca flour and 15% of Chinese potato treatment on which a bromatological analysis was carried out, obtaining as a result values such as Calcium mg/100g 3335.479, Ashes 17.6%, Crude fiber 15.9%, Phosphorus mg/100g 382.24, Fat 11.9%, Moisture 6.2% and Protein 17.8%. As a conclusion, it can be determined that the addition of alternative raw materials such as Yucca and Chinese potato represent a viable contribution on the weight variable providing alternatives on nutrition to the animal farming industry in the Pastaza area